Phonon–Phason Coupling Strength in a Tsai-Type Ag–In–Yb Icosahedral Quasicrystal - Zhang, Jinjia; Tokumoto, Yuki; Edagawa, Keiichi; Zhou, Jintao (MATERIALS TRANSACTIONS, 2023)
Owing to the quasiperiodic order, one independent term in the elasticity of quasicrystals (phonon–phason coupling) is characteristic of quasicrystals. It is not seen in conventional crystals and has continued to be a significant subject in the research field of quasicrystals. Recently, a novel method was applied to a Mackay-type Al–Pd–Mn icosahedral quasicrystal to prove the existence of phonon–phason coupling and to evaluate its strength based on the elasticity of quasicrystals. This study applied the method to a Tsai-type Ag–In–Yb icosahedral system to evaluate its phonon–phason coupling strength. We applied phonon strain to the quasicrystal at a temperature with active phason, and the induction of phason strain was successfully detected and evaluated using powder X-ray diffraction. We evaluated the phonon–phason coupling elastic constant of the Ag–In–Yb icosahedral quasicrystal to be 0.17 ± 0.04 GPa by quantitatively comparing the measured induced phason strain with our calculation results.